OGG1 Inhibition Reduces Acinar Cell Injury in a Mouse Model of Acute Pancreatitis - Zoltán Hajnády; Máté Nagy-Pénzes; Máté A. Demény; Katalin Kovács; Tarek El-Hamoly; József Maléth; Péter Hegyi; Zsuzsanna Polgár; Csaba Hegedűs; László Virág (Biomedicines, 2022)
Acute pancreatitis (AP) is a potentially life-threatening gastrointestinal disease with a complex pathology including oxidative stress. Oxidative stress triggers oxidative DNA lesions such as formation of 7,8-dihydro-8-oxo-2′-oxoguanine (8-oxoG) and also causes DNA strand breaks. DNA breaks can activate the nuclear enzyme poly(ADP-ribose) polymerase 1 (PARP1) which contributes to AP pathology. 8-oxoG is recognized by 8-oxoG glycosylase 1 (OGG1) resulting in the removal of 8-oxoG from DNA as an initial step of base excision repair. Since OGG1 also possesses a DNA nicking activity, OGG1 activation may also trigger PARP1 activation. In the present study we investigated the role played by OGG1 in AP. We found that the OGG1 inhibitor compound TH5487 reduced edema formation, inflammatory cell migration and necrosis in a cerulein-induced AP model in mice. Moreover, TH5487 caused 8-oxoG accumulation and reduced tissue poly(ADP-ribose) levels. Consistent with the indirect PARP inhibitory effect, TH5487 shifted necrotic cell death (LDH release and Sytox green uptake) towards apoptosis (caspase activity) in isolated pancreatic acinar cells. In the in vivo AP model, TH5487 treatment suppressed the expression of various cytokine and chemokine mRNAs such as those of TNF, IL-1β, IL1ra, IL6, IL16, IL23, CSF, CCL2, CCL4, CCL12, IL10 and TREM as measured with a cytokine array and verified by RT-qPCR. As a potential mechanism underlying the transcriptional inhibitory effect of the OGG1 inhibitor we showed that while 8-oxoG accumulation in the DNA facilitates NF-κB binding to its consensus sequence, when OGG1 is inhibited, target site occupancy of NF-κB is impaired. In summary, OGG1 inhibition provides protection from tissue injury in AP and these effects are likely due to interference with the PARP1 and NF-κB activation pathways.